2018
DOI: 10.1021/acs.langmuir.7b03885
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Synthesis of High-Quality Cu2ZnSnS4 Nanocrystals and Their Thermal Annealing Characteristics

Abstract: Copper zinc tin sulfide (CZTS) nanocrystal inks are promising candidates for the development of cheap, efficient, scalable, and nontoxic photovoltaic (PV) devices. However, optimization of the synthetic chemistry to achieve these goals remains a key challenge. Herein we describe a single-step, aqueous-based synthesis that yields high-quality CZTS nanocrystal inks while also minimizing residual organic impurities. By exploiting simultaneous redox and crystal formation reactions, square-platelet-like CZTS nanocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 79 publications
(115 reference statements)
0
16
0
Order By: Relevance
“…However, the examples of aqueous syntheses of CZTS NCs are quite rare 53,54 typically yielding strongly agglomerated NCs and providing no reliable means for the control of the NC size and size distribution. Only recently aqueous syntheses with Sn 2 S 6 4− complex anions as capping ligands were reported to produce stable and uniform CZTS NCs 55,56 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the examples of aqueous syntheses of CZTS NCs are quite rare 53,54 typically yielding strongly agglomerated NCs and providing no reliable means for the control of the NC size and size distribution. Only recently aqueous syntheses with Sn 2 S 6 4− complex anions as capping ligands were reported to produce stable and uniform CZTS NCs 55,56 .…”
Section: Introductionmentioning
confidence: 99%
“…In their work, however, they prepared the tin chalcogenide complex by dissolving metallic tin and elemental sulfur in ammonium sulfide solution, a rather inefficient method prone to poor reproducibility due to oxidation of metallic tin without the use of a glovebox. Ritchie et al showed that the redox process to form the tin chalcogenide complexes had poor stability, which may complicate larger scale applications [29]. Instead, a dissociative process can be used to make the tin chalcogenide complex as per the method of Krebs involving dissolution of tin(IV) sulfide into aqueous ammonium sulfide solution [25] adopted for CZTS film fabrication by Ritchie et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…Ritchie et al showed that the redox process to form the tin chalcogenide complexes had poor stability, which may complicate larger scale applications [29]. Instead, a dissociative process can be used to make the tin chalcogenide complex as per the method of Krebs involving dissolution of tin(IV) sulfide into aqueous ammonium sulfide solution [25] adopted for CZTS film fabrication by Ritchie et al [29]. In both of these CZTS aqueous nanoink works [28,29], thiourea was used as a supplementary complexing-stabilizing agent [30,31,32] for the soluble copper and zinc salts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations